MEDIA RICHNESS ON INSTAGRAM INFLUENCES TOWARDS CONSUMER PURCHASE INTENTION: EXPLORING THE MODERATING EFFECT OF BRAND EQUITY - Muhammad Asyraf Hasim; Mohd Fikri Ishak; Nurul Nadia Abdul Halim; Arman Hj Ahmad; Putu Ngurah Suyatna (Dinasti International Journal of Education Management And Social Science, 2020)
Social media has become a widely-adopted technology since it being introduced to the world, affecting businesses in myriad ways. Majority of companies nowadays started to invest on social media marketing in regards to the ability of this marketing initiative lead to better profitability. However, only few studies have looked at the empirical link between media richness from social media i.e. Instagram and purchase intention among consumers. This paper discusses the influences of media richness on Instagram towards consumers’ intention to purchase mediated by brand equity. This study was conducted utilising survey research method, aiming to create better understanding of consumer intention to purchase as being influenced by social media richness. A total of 537 undergraduate students in Kuala Lumpur, Malaysia age 19 to 24 years old took part in this study as respondents. The respondents are exposed to Instagram postings on similar products for sale. Partial least square structural equation modelling (PLS-SEM) applied to fit the data in the hypothesised model. The outcome of study is useful to both researchers and business practitioners to understand the importance of social media richness specifically utilising Instagram as business platform. Future study should consider on discovering different perspective of media richness involving other types of social media.